Penyuluhan Hukum Pencegahan Tindak Kekerasan dalam Rumah Tangga di Kopen RT. 03 RW. 07 Ngadirejo Kartasura - Julijanto, Muhammad; Anwaruddin, Anwaruddin; Lisma, Lisma; Damayanti, Meliana (Proceedings of Annual Conference on Community Engagement, 2018)
Domestic violence is still a social problem like the iceberg. The surface looks a little, but if you explore it further the case is a lot. How prevention efforts are carried out, so that the quality of the household, will be more physically and spiritually prosperous. Conversely, if the level of domestic violence is high, it will affect the harmony and quality of households affected. The purpose of the implementation of legal counseling is to assist and facilitate the community for independence in understanding the problem of domestic violence (KDRT), Providing understanding and knowledge that can be accessed by the community. Provide skills to prevent domestic violence.